Regulating Reproductive Technologies in Canada - Mykitiuk, Roxanne (2002)
This chapter will identify and examine the major legal issues raised by the development and proliferation of technologies involved in assisted reproduction. It will review the application of existing legal principles, statutes and common law rules to these issues, and will illustrate the uncertainty present in the current legal regime in Canada. The chapter will then evaluate the need for a unified regulatory framework for reproductive technologies ( RTs ).' While the focus of the chapter is an identification and review of the legal issues, it should be understood that these are shaped in a moral, ethical and social context